Species Abundance and Body Size Relationship of Bird Assemblages at Selected Sites in Western Sarawak - Ahmad Fitri, Aziz (Universiti Malaysia Sarawak (UNIMAS), 2014)
The Energy Equivalence Rule (EER) is an unsettled issue in ecology. This rule stated that the amount of energy that each species used in a population is independent to its body size. A study on the relationship between abundance and body size of bird assemblages in Western Sarawak was conducted. Abundance data of bird assemblages from seven selected sites in Western Sarawak were used to produce slope of regression line of log absolute species abundance against log average body mass by using SPPS Version 21.0 software. Data from all selected sites were combined to represent bird assemblages in Western Sarawak and the slope produced was -0.216. The slopes obtained for each site were 0.808, -0.080, -0.258, -0.067, -0.161, -0.072 and -0.237, respectively. Statistical analysis shows that the slope of combined data has no significant difference with -0.75 as expected under the EER. Thus, this study shows that the EER can be applied as a general rule of community structure.